A Review on the Synthesis and Pharmacological Activity of Heterocyclic Compounds - Baranwal, Jyoti; Kushwaha, Smriti; Singh, Swastika; Jyoti, Archana (Current Physical Chemistry, 2023)
Biologically active compounds play a very important role in our daily life. Almost all biologically active compounds contain heteroatoms and among these, a major portion is heterocycles. Heterocycles are a significant component in drug development programs. Drugs containing a heterocyclic moiety are highly valued resources in the fight against human and animal diseases. Some of these compounds are utilized as anticonvulsants antivirals, anti-inflammatory, and central vasodilators, while others are used as nontherapeutic anthelmintics, diuretics, anti-hypertensives, uricosurics, fungicides, bactericides, and herbicides. In this review, we have discussed the chemistry of heterocyclic compounds such as Quinoxaline, Triazole, Pyrimidine, Pyridine, Oxadiazole, Thiazole, Indole, and Azepine. Besides some of their recent synthetic methodologies, their pharmaceutical importance is also discussed. Undoubtedly, the contents of this review will motivate readers to do more novel work in this area which will accelerate the journey toward the exploration of the pharmacological activity of heterocyclic compounds.
Keywords: pharmacological activity